Monocular, Real-Time Surface Reconstruction using Dynamic Level of Detail - Zienkiewicz,J; Tsiotsios,C; Davison,AJ; Leutenegger,S (IEEE, 2016)
We present a scalable, real-time capable method for robustsurface reconstruction that explicitly handles multiplescales. As a monocular camera browses a scene, ouralgorithm processes images as they arrive and incrementallybuilds a detailed surface model. While most of theexisting reconstruction approaches rely on volumetric orpoint-cloud representations of the environment, we performdepth-map and colour fusion directly into a multi-resolutiontriangular mesh that can be adaptively tessellated usingthe concept of Dynamic Level of Detail. Our method relieson least-squares optimisation, which enables a probabilisticallysound and principled formulation of the fusionalgorithm. We demonstrate that our method is capable ofobtaining high quality, close-up reconstruction, as well ascapturing overall scene geometry, while being memory andcomputationally efficient.